The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/pssr.201600350
|View full text |Cite
|
Sign up to set email alerts
|

Structure and orbital ordering of ultrathin LaVO3probed by atomic resolution electron microscopy and Raman spectroscopy

Abstract: Orbital ordering has been less investigated in epitaxial thin films, due to the difficulty to evidence directly the occurrence of this phenomenon in thin film samples. Atomic resolution electron microscopy enabled us to observe the structural details of the ultrathin LaVO3 films. The transition to orbital ordering of epitaxial layers as thin as ≈4 nm was probed by temperature‐dependent Raman scattering spectroscopy of multilayer samples. From the occurrence and temperature dependence of the 700 cm–1 Raman acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…,Lu, which reveal temperature-induced magnetization reversals [41] as a result of the coupling of spin and orbital degrees of freedom of the t 2g valence electrons [42][43][44][45][46][47]. This class of compounds has interesting phase diagrams with two complementary spinorbital ordered phases and a pure orbital-ordered phase [48][49][50][51][52][53][54]. Remarkably, the C-type spin and G-type orbital ordered phase in La 1−x Sr x VO 3 , Pr 1−x Ca x VO 3 and Y 1−x Ca x VO 3 is robust up to high-doping concentrations and also the metalinsulator transition takes place only at quite substantial doping [55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%
“…,Lu, which reveal temperature-induced magnetization reversals [41] as a result of the coupling of spin and orbital degrees of freedom of the t 2g valence electrons [42][43][44][45][46][47]. This class of compounds has interesting phase diagrams with two complementary spinorbital ordered phases and a pure orbital-ordered phase [48][49][50][51][52][53][54]. Remarkably, the C-type spin and G-type orbital ordered phase in La 1−x Sr x VO 3 , Pr 1−x Ca x VO 3 and Y 1−x Ca x VO 3 is robust up to high-doping concentrations and also the metalinsulator transition takes place only at quite substantial doping [55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, this was examined in high-pressure studies, which showed that the ground state of RVO 3 can be altered under sufficient pressure [43][44][45]. This lattice coupling was also inspected in thin films of LaVO 3 [46][47][48][49] and PrVO 3 [50,51], where biaxial epitaxial strain was utilized to modify their ordering temperatures.…”
Section: Introductionmentioning
confidence: 99%